(untitled) (Revista Nacional de Odontología, 2017)
Introduction: Gingival recession is a clinical finding after the apical displacement of the gingival margin; it can be localized or generalized and be associated with one or several dental surfaces, causing both aesthetic and functional compromise according to its extension. Aim: To describe Miller’s Class I gingival recession treatment using subepithelial connective tissue graft and coronally positioned flap. Materials and methods: Descriptive clinical case report of a male patient who consulted for an aesthetic issue in the upper jaw area. The appropriate anamnesis procedures were performed, in which no relevant syste- mic history was identified. Then clinical examination with a diagnosis, planning and administration of the treatment, and postsurgical controls were carried out. Results: Based on a diagnosis of Miller’s Class I recession located in dental organs 13 and 14, we decided to implement the technique of subepithelial connective tissue graft and coronally positionedflap, with which complete radicular covering, favorable tissue response, and the patient’s aesthetic satisfaction were achieved. Conclusions: The connective tissue graft, in combination with the coronally positioned flap, is viable at the level of radicular covering in gingival recessions in multiple teeth with an inadequate amount of keratinized gingiva. This shows that it is a predictable technique that satisfies the aesthetic needs of the patient.